2017
DOI: 10.5209/reve.54916
|View full text |Cite
|
Sign up to set email alerts
|

La localización sectorial del cooperativismo: una aproximación a nivel territorial español

Abstract: La posibilidad de cambiar los modelos de desarrollo socioeconómicos hacia otros más sostenibles y responsables está siendo planteada tanto por parte de investigadores como de diferentes instituciones, con una importancia que se ha visto incrementada a partir de la última crisis. En este escenario, la economía social se presenta como una oportunidad de cambio y de contribución a estos nuevos modelos, dado los principios y valores que la definen y sobre los que basa su funcionamiento; por ello, es relevante la a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
6
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 5 publications
2
6
0
1
Order By: Relevance
“…The analysis above conforms to the study by Pérez and Valiente (2017) which points out cooperatives' sectorial and regional diversity. As the authors state, major homogeneity is found in the services sector, even though it is not possible to argue that a behaviour-only pattern exists.…”
Section: Cooperatives Descriptive Analysissupporting
confidence: 74%
“…The analysis above conforms to the study by Pérez and Valiente (2017) which points out cooperatives' sectorial and regional diversity. As the authors state, major homogeneity is found in the services sector, even though it is not possible to argue that a behaviour-only pattern exists.…”
Section: Cooperatives Descriptive Analysissupporting
confidence: 74%
“…In contrast, club 4, with a decreasing trajectory, is made up of regions whose predominant sector of activity is the service sector: Madrid, the Balearic Islands or the Canary Islands, joined with Cantabria and Asturias. These results coincide, although using a different methodology, with those of Pérez and Valiente (2017). Sala-Ríos et al ( 2020) also explain that Madrid has a significant presence of administration and services and that the Balearic Islands is one of the largest tourist destinations in Spain, which requires a large number of service companies.…”
Section: Convergence Of Cooperative Employment Related To Total Emplo...mentioning
confidence: 58%
“…In Spain, several works stand out, such as Sala-Ríos et al ( 2020), Clemente et al (2009), and Pérez and Valiente (2017). The work by Sala-Ríos et al ( 2020) addresses employment generated by cooperatives and their link with the territory, specifically with the regions (17 NUT-2 regions in Spain), between 2003 and 2019.…”
Section: Cooperatives and Territorymentioning
confidence: 99%
“…The advantages between the territory and the presence of cooperatives feed back to each other. Cooperatives’ greater sensitivity and identity with the territory and their democratic and participative principles and values reinforce their commitment to the local community (Pérez & Valiente, 2017; Vo, 2017). Moreover, cooperatives’ social objectives, their greater stability in employment and greater engagement with sustainable and responsible consumption and growth enhance local development (Gallego‐Bono & Chaves‐Avila, 2020; Melian & Campos, 2010; Pérez & Valiente, 2017, 2019; Tarazona & Albors, 2005).…”
Section: Resultsmentioning
confidence: 99%